Implementation of a Distribution Static Compensator D-STATCOM: Hardware and Firmware Description - Ortiz Castrillón, José Robinson; Benavides Córdoba, Santiago; Cano Quintero, Juan Bernardo; Muñoz Galeano, Nicolás; Lopez Lezama, Jesus Maria (Scientia et Technica, 2019)
This paper describes the implementation of a distribution static power compensator (D-STATCOM) for reactive compensation in electric distribution networks. A three-phase inverter of six pulses with two levels was developed. Hardware implementation of different stages (sensors, power switching, passive elements, and processor) is fully described. Firmware that allows D-STATCOM operation was implemented on a TMS3202F DSP (Texas Instruments) using a modular approach. Correct operation of the D-STATCOM prototype is verified with experimental results.